Conflict 2023–2025: An Analysis of International Humanitarian Law and Challenges Settlement by the International Criminal Court (ICC) - Kurdi, Kurdi; Arbani, Muhammad (IHSA Institute, 2026)
The conflict between Israel and Palestine is a prolonged conflict that continues to this day. The conflict peaked again on October 7, 2023 and caused many casualties on the Palestinian side. This study aims to find out about Israel's military aggression against Palestine in 2023-2025 based on international humanitarian law. In addition, it also aims to analyze the role and challenges of the ICC in resolving Israeli-Palestinian aggression based on international law. This research is a type of normative legal research with a statutory regulatory approach and a conceptual approach. The results of the study show that in the 2023-2025 Israeli-Palestinian conflict, Israel violated the principles of international humanitarian law and also the rules of international law itself as regulated in the Geneva Conventions and their additional protocols, as well as the Rome Statute which regulates its enforcement. To resolve the conflict, the ICC plays a role by investigating the Palestinian situation and issuing arrest warrants against those responsible for enforcing international humanitarian law. However, in its implementation there are challenges faced by the ICC, namely the ICC does not have an executive force authorized to carry out the warrants that have been issued, Israel is not a party to the Rome Statute, and there is great pressure from various countries that support Israel. The suggestion based on the results of the study is that the ICC must act independently and not be influenced by political pressure from any country, so that it can enforce humanitarian law as it should